Carbohydrate Chemistry. - Ferrier, R. J. (Specialist periodical report., 2000)
Carbohydrate Chemistry provides review coverage of all publications relevant to the chemistry of monosaccharides and oligosaccharides in a given year. The amount of research in this field appearing in the organic chemical literature is increasing because of the enhanced importance of the subject, especially in areas of medicinal chemistry and biology. In no part of the field is this more apparent than in the synthesis of oligosaccharides required by scientists working in glycobiology. Clycomedicinal chemistry and its reliance on carbohydrate synthesis is now very well established, for example,